The production of high purity hexagonal MoO3 through the acid washing of as-prepared solids - Ramli, Irmawati; Masuri, Shafizah (IJENS Publishers, 2009)
Highly pure and crystalline h-MoO3 nanocrystals in the form of well-faceted straight hexagonal rods were successfully synthesised from an acid-base titration method. The formation of metastable h-MoO3 was due to the addition of a high H+concentration to a basic molybdenum solution. Precipitates were formed at a pH range of 1.95-2.10. X-ray diffraction (XRD)analysis confirmed that the obtained solids were hexagonal MoO3, while their morphology was observed using scanning electron microscopy (SEM). The fabricated rods have a BET total surface area of ~3m2g-1, with crystallite sizes ranging from 33 to 46 nm.